Clinical Outcomes in Patients With Type 2 Diabetes Mellitus and Peripheral Artery Disease: Results From the EXSCEL Trial. (December 2019) - Badjatiya, Anish; Merrill, Peter; Buse, John B.; Goodman, Shaun G.; Katona, Brian; Iqbal, Nayyar; Pagidipati, Neha J.; Sattar, Naveed; Holman, Rury R.; Hernandez, Adrian F.; Mentz, Robert J.; Patel, Manesh R.; et al.
Abstract : Background: Recent trials have identified anti–diabetes mellitus agents that lower major adverse cardiovascular event (MACE) rates, although some increase rates of lower-extremity amputation (LEA). Patients with peripheral artery disease (PAD) have greater incidence of diabetes mellitus and risk for LEA, prompting this investigation of clinical outcomes in patients with diabetes mellitus and PAD in the EXSCEL trial (Exenatide Study of Cardiovascular Event Lowering). Methods: EXSCEL evaluated the effects of once-weekly exenatide (a GLP-1 [glucagon-like peptide-1] receptor agonist) versus placebo on the rates of the primary composite MACE end point (cardiovascular death, myocardial infarction, or stroke) among patients with type 2 diabetes mellitus. In this post hoc analysis, we assessed the association of baseline PAD with rates of MACE, LEA, and the effects of exenatide versus placebo in patients with and without PAD. Results: EXSCEL included 2800 patients with PAD (19% of the trial population). These individuals had higher unadjusted and adjusted rates of MACE compared with patients without PAD (13.6% versus 11.4%, respectively) as well as a higher adjusted hazard ratio (adjusted hazard ratio, 1.13 [95% CI, 1.00–1.27]; P =0.047). Patients with PAD had higher all-cause mortality (adjusted hazard ratio 1.38 [95% CI, 1.20–1.60]; P <0.001) and more frequent LEA (adjusted hazard ratio 5.48 [95% CI, 4.16–7.22]; P <0.001). Patients treated with exenatide or placebo had similar rates of MACE and LEA, regardless of PAD status. Conclusions: EXSCEL participants with PAD had higher rates of all-cause mortality and LEA compared with those without PAD. There were no differences in MACE or LEA rates with exenatide versus placebo. Clinical Trial Registration URL: https://www.clinicaltrials.gov . Unique identifier: NCT01144338.